Kerentanan Pekerja Immaterial dalam Industri Komersialisasi Vlog - Pratitis, Ayu Laras (Masyarakat: Jurnal Sosiologi, 2017)
Recent studies on video blog (vlog) focuses on participatory culture and the relationship between the audience and vlog producer. This study will analyse the commercialization of vlog which have impacted immaterial workers in the line of production. This paper argues the the commercialization of vlog has allowed the emergence of immaterial workers, vlogger and non-vlogger groups. Both groups are involved in an unstable social relation towards the corporate. Therefore, causing different forms of susceptibility between the two groups. By using qualitative methods, various data from in-depth interviews, observation, and secondary data have shown that the unstable relation between non-vlogger and the corporate have eventually leads to a state of absence: the halting of workers protection, rising wages cost, the limiting of working hours, the demand of higher working skills, the increase of associati